Labour tax reforms, cross-country coordination and the monetary policy stance in the euro area: a structural model-based approach - Jacquinot, Pascal; Lozej, Matija; Pisani, Massimiliano (Frankfurt am Main, 2018)
"We evaluate the effects of permanently reducing labour tax rates in the euro area (EA) by simulating a large-scale open economy dynamic general equilibrium model. The model features the EA as a monetary union, split in two regions (Home and the rest of the EA - REA), the US, and the rest of the world, region-specific labour markets with search and matching frictions, and public employment. Our results are as follows. First, a permanent reduction in labour tax rates in the Home region would have stimulating effects on domestic economic activity and employment. Second, reducing labour tax rates simultaneously in both Home and REA would have additional expansionary effects on the Home region. Third, in the short run the expansionary effects on the EA economy of a EA-wide tax reduction are enhanced if the EA monetary policy is accommodative."